Highly anisotropic corrugated laminates deflection under uniform pressure. (15th October 2016) - Thurnherr, C.; Mirabito, Y.; Kress, G.; Ermanni, P.
Abstract: Corrugated laminates with large corrugation amplitude have highly anisotropic stiffness properties. Here, the bending response of rectangular corrugated laminates to homogeneous transverse pressure is investigated. The center-point deflection of thin laminates with high corrugation amplitude is controlled by the higher bending-stiffness value alone. Simple formulas for calculating the center-point deflection are developed from beam formulas by replacing beam bending stiffness with plate bending stiffness and the line load with pressure. A finite-element model is used to verify the results and to illustrate the peculiar load-carrying action of the highly anisotropic plate. Further an error analysis is presented to indicate for which stiffness and aspect ratios the beam-equation modeling approach is valid and can be used for preliminary design.